2019
DOI: 10.1111/jdv.15934
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized controlled trial comparing treatment efficacy and tolerance of picosecond alexandrite laser with a diffractive lens array and triple combination cream in female asian patients with melasma

Abstract: Background Recent evidence suggests melasma to be a photoaging disorder. Triple combination creams (TCC: fluocinolone acetonide 0.01%, hydroquinone 4% and tretinoin 0.05%) remain the gold standard treatment. Picosecond alexandrite laser treatment using a diffractive lens array (DLA) has been identified to be effective for improving photoaging conditions. Objective We aimed to compare the efficacy and tolerance of the picosecond alexandrite laser with those of DLA and TCC in female Asian patients with melasma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 30 publications
3
22
0
1
Order By: Relevance
“…Within the population of patients who developed PIH, the rate of underlying melasma was 83%. Although PS laser has been used to treat melasma in seven studies (one case series; one prospective open label trial; four prospective, randomized, split‐face trials; and one randomized control trial) [33–39], its use as monotherapy for this condition is not considered standard of care due to the well‐known risks of laser treatment for melasma [6]. Taking into account all of the above, the rate of PIH reported in this study is likely still reflective of a short picosecond pulse duration advantage.…”
Section: Discussionmentioning
confidence: 95%
“…Within the population of patients who developed PIH, the rate of underlying melasma was 83%. Although PS laser has been used to treat melasma in seven studies (one case series; one prospective open label trial; four prospective, randomized, split‐face trials; and one randomized control trial) [33–39], its use as monotherapy for this condition is not considered standard of care due to the well‐known risks of laser treatment for melasma [6]. Taking into account all of the above, the rate of PIH reported in this study is likely still reflective of a short picosecond pulse duration advantage.…”
Section: Discussionmentioning
confidence: 95%
“…We intended to use a conservative technique by performing only two passes of treatment without pulse overlapping in our study while treatment for rejuvenation and atrophic scar purposes is normally done with a more aggressive technique (over 2 passes with 15-20% of pulse overlapping) [20,21]. The benefit of fractional picosecond laser over the full-beam for the treatment of melasma has yet to be confirmed since most of the previous studies were not designed to compare this efficacy [5][6][7]19]. To the best of our knowledge, the present study is the first study to demonstrate that the full-beam (flat optics) 755-nm picosecond laser provides less downtime and treatment discomfort and offers a comparable clinical outcome and lower incidence of PIH than the fractioned one.…”
Section: Discussionmentioning
confidence: 99%
“…Picosecond lasers are currently available with laser outputs of 532-, 670-, 755-, 785-, and 1064-nm. At present, there have been limited data published about their efficacy in the treatment of melasma [2,[5][6][7]. More recently, fractionated picosecond handpieces have been developed for the purpose of resurfacing and rejuvenation.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous reports with a variety of fractionated and non-fractionated modalities have shown limited success, the risks of rapid recurrence, rebound hyperpigmentation, and developing mottled hypopigmentation are significant. To date, picosecond laser has been used to treat melasma in one case series; one prospective open-label trial; four prospective, randomized, split-face trials; and one randomized controlled trial involving a cumulative total of 140 patients [56][57][58][59][60][61][62]. Choi et al [57] conducted a randomized single-blind split-face clinical trial involving 39 patients with melasma.…”
Section: Melasmamentioning
confidence: 99%
“…Additional studies have compared modified Kligman triple combination cream and nanosecond Nd:YAG (QSYAG) against picosecond alexandrite laser (PSAL) with or without diffractive lens array respectively [59,60]. In the first comparison, Wang et al randomized three groups of subjects to receive either three treatments of fractionated PSAL at 4-week intervals (Group A), five treatments of fractionated PSAL at 4-week intervals (Group A2), or triple combination cream consisting of 0.01% fluocinonide acetonide, 4% hydroquinone, and 0.05% tretinoin applied nightly for 8 weeks, then twice weekly for 6 weeks, then once weekly for 6 weeks (Group B) [60]. The investigators reported significant improvements in MASI score in all groups at the final evaluation time point which was set at 1 month following the final treatments for group A2 (3 months following the final treatments for group A1).…”
Section: Comparative Studies and Controversiesmentioning
confidence: 99%